Military Tribunate in the Careers of Roman Senators of the Severan Period. Part 3: Higher Military Command (Legatus Legionis, Praepositus, Dux) - Okoń, Danuta (Polskie Towarzystwo Filologiczne, 2021)
During the 42 years of the rule of the Severan dynasty (193–235), several thousand people with the title of military tribune probably served in the army of the Roman Empire. Some of them then entered the Roman Senate, starting a public career (which was often a long-term career) and forming the core of the State government. The aim of this paper is to answer the following questions: how many military tribunes took up higher military functions in their careers: legatus legionis, praepositus, dux; what were the rules for assuming these functions and the competences required to perform them; whether any of the senators who held the military tribunate in the Severan period can be defined as vir militaris and whether the Roman army was commanded by dilettantes.